The economic impact of higher education institutions in Ireland: evidence from disaggregated input–output tables. Issue 9 (2nd September 2017) - Zhang, Qiantao; Larkin, Charles; Lucey, Brian M.
Abstract : While there has been a long history of modelling the economic impact of higher education institutions (HEIs), little research has been undertaken in the context of Ireland. This paper provides, for the first time, a disaggregated input–output table for Ireland's higher education sector. The picture painted overall is a higher education sector that adds considerable gross value to the national economy, whether via state or other income. In 2010–2011, the gross income of Irish HEIs, as a total of €2.6 billion, generated gross output nationwide of €10.6 billion. This study also contributes to the major challenges facing the sector in a post-Bailout environment.